Sosialisasi Pentingnya Etika Bisnis dalam Aktivitas Produksi UMKM Telur Asin di Kelurahan Penanae Kota Bima - Kartin Aprianti; Nufus Al Maidah; Sarina Sarina; Fauzan Fauzan; Indah Syari; Nurbaity Raodatun Nadita (Fakultas Teknik Universitas Cenderawasih, 2025)
This research was conducted with the aim of helping MSME actors, particularly salted egg MSMEs in Penanae Village, to understand the importance of applying business ethics principles in their operations to create a good business system. This is also important to establish a healthy relationship between MSME actors and consumers. The method offered to partners/UMKM is in the form of education/socialization using LEAFLETS conducted door to door. The material provided in the leaflet includes discussions on (1) The Role of Ethics in Business for UMKM actors, (2) Benefits of Business for UMKM actors, (3) Application of ethical principles in business activities such as finance, marketing, production, and HR. The results of the education show a change in participants' responses, with a better understanding of attitudes and knowledge regarding business ethics.